FEATURES OF THE OCCURRENCE OF DENTAL DISEASES IN CHILDREN - Khayitova Mokhinur Dzhuraevna (Лучшие интеллектуальные исследования, 2024)
Resume. The likelihood of developing diseases varies from person to person, but they most often occur in people with risk factors. Such factors include features of structure, physiology, heredity in individuals, as well as living conditions, diet, lifestyle, habits and inclinations that can contribute to the development of diseases.